Continuing professional development and special librarians in Jamaica. Issue 6 (11th July 2019) - Robinson, Marsha-Gay
Abstract : Purpose: The purpose of this paper is to examine the continuing professional development (CPD) activities undertaken by special librarians in Jamaica, their motivation, the challenges faced and the areas of interest for professional development. Design/methodology/approach: Special librarians working in Jamaica were surveyed using an online questionnaire which was disseminated via e-mail. Findings: The study indicates that special librarians in Jamaica were engaged in both formal and informal CPD activities. They were motivated by factors such as keeping up to date with changes in librarianship and personal satisfaction. Challenges to participating in CPD include, lack of funding, time constraints and lack of worthwhile options. Areas of interest for CPD were mainly information technology-based. Research limitations/implications: The study was limited to the contact lists of the special libraries section of the Library and Information Association of Jamaica (LIAJA) and the Government Library and Information Network of the Jamaica Library and Information Network (JAMLIN). Practical implications: The results have implications for the planning and implementation of continuing professional activities for Jamaica's special librarians. It also fills a gap in library literature regarding the continuing professional activities of special librarians. Originality/value: The paper is one of few studies focusing on the CPD activities of special librarians undertaken in a developing country.